Association of Oxidative Stress Markers with Cholelithiasis - Omer S.Sadiem; Mohamed A. Taher; Seenaa S. Amin (College of Pharmacy University of Baghdad, 2017)
Oxidative stress markers are of important diagnostic parameters for many disorders including cholelithiasis. This present study has aimed to assess the state of oxidative stress in symptomatic radiographically confirmed (Cholelithiasis) patients by measuring two parameters used as oxidative stress parameters which are serum myeloperoxidase (MPO) and superoxide dismutase (SOD). This study was carried out on 100 patient diagnosed as (Cholelithiasis) patients with 30 age and sex matched healthy controls by measuring serum (MPO) and (SOD) by ELIZA technique .Results showed significantly decrease in antioxidant enzyme(SOD) and increase in serum level of (MPO) comparing with controls. Keywords: Cholelithiasis , Oxidative stress, MPO, SOD